MEMORY AND CENTRALITY IN RESENDE - Silva, William Ribeiro (Mercator, 2020)
This article discusses the role of the Main Center in a medium-sized city undergoing urban restructuring at the interface between space and time and its different locational logics and dynamics. Our approach includes mapping the spatiality of the economic activities of Resende’s downtown and Campos Elíseos, especially bank branches and public administration buildings. The research materials were photographic records and their respective historical interpretations, reported memories given through interviews, and publications by memorialists, historians, and official sources, among others. The aim was to reconstitute the “present of the past”, following a chronological path from the time of the peak and decline of coffee production, at the beginning and mid-nineteenth century, respectively, to the formation of the Main Center of Campos Elíseos in the mid-twentieth century. The discussion has three parts: the formation of the Historical Center of Resende; the Center crossing the river, which debates the formation of the Main Center in Campos Elíseos, and finally, a reflection on the spatial struggle of urban centrality in a medium-sized city. Keywords : Centrality, Memory, Intermediary Cities, Central Area.